Pengaruh Brand Image, Kualitas Produk dan Endorsement Selebriti Instagram terhadap Minat Beli Konsumen pada Produk Skin Care MS GLOW - Hasanah, Ulfatul; Giyartiningrum, Eko (Journal Competency of Business, 2021)
This study aims to determine the effect of brand image, product quality, celebrity endorsements on Instagram on consumer buying interest in MS GLOW skin care products. Using the survey method, the sample in this study amounted to 100 respondents who were consumers of MS GLOW skin care products. The data analysis technique used multiple linear regression analysis with the SPSS program. Based on the results of multiple linear regression, brand image has a significant effect on consumer buying interest, product quality has a significant effect on consumer buying interest, and celebrity endorsements on Instagram have no significant effect on consumer buying interest.